Interaction of GPER-1 with the endocrine signaling axis in breast cancer - Molina Calistro, Luis; Arancibia, Yennyfer; Olivera, Marcela Alejandra; Domke, Sigrid; Torres, Rodrigo Flavio (Frontiers in Endocrinology, 2025)
G Protein-Coupled Estrogen Receptor 1 (GPER-1) is a membrane estrogen receptor that has emerged as a key player in breast cancer development and progression. In addition to its direct influence on estrogen signaling, a crucial interaction between GPER-1 and the hypothalamic-pituitary-gonadal (HPG) axis has been evidenced. The novel and complex relationship between GPER-1 and HPG implies a hormonal regulation with important homeostatic effects on general organ development and reproductive tissues, but also on the pathophysiology of cancer, especially breast cancer. Recent research points to a great versatility of GPER-1, interacting with classical estrogen receptors and with signaling pathways related to inflammation. Importantly, through its activation by environmental and synthetic estrogens, GPER-1 is associated with hormone therapy resistance in breast cancer. These findings open new perspectives in the understanding of breast tumor development and raise the possibility of future applications in the design of more personalized and effective therapeutic approaches.